Development of Asphalt Pavement Temperature Model for Tropical Climate Conditions in West Bali Region. (2015) - Ariawan, I. Made Agus; Subagio, Bambang Sugeng; Setiadji, Bagus Hario
Abstract: The temperature within the asphalt pavement layers varies due to the influence ofenvironmental factors including air temperature, humidity, solar radiation, wind speed, and the reflectance of pavement surface. The temperature distribution on the cross section of asphalt pavement layer is considerably important in connection with the strength characteristics of various asphalt pavement designs. This study develops model of asphalt pavement temperature for tropical climate conditions in Indonesia which has a specific climate characteristics. Indonesia is located on a narrow range of latitudes (6 0 North - 11 0 South) and is crossed by the equator. Indonesia has a tropical climate and experiences lots of sunlight, rainfalls and high humidity throughout the year. The national road of Denpasar - Gilimanuk (Km 102) segment, Negara regency in the western of Bali is selected as a case study area. Thermocouples sensors equipped with data loggers were installed in various depths. Based on the SAGA Technology program, the temperatures were recorded every 30 minutes. About 336 observational data were recorded which include hourly variations of temperature and humidity as well as pavement temperature in various depth. It was found that there was a strong positive linear correlation (r > 0.8) between the air temperature and the temperature of the asphalt pavement. On the other hand, a strong negative linear correlation (r > -0.8) between the humidity and temperature of the pavement was found. Linear regression models were developed to predict the temperature of the asphalt pavement by using temperature and humidity as independent variables. The results indicated that the model has a good estimation accuracy.